Valuasi Ekonomi Dampak Eksploitasi Air Tanah Oleh PT. Tirta Investama Terhadap Sektor Pertanian di Kecamatan Trucuk Kabupaten Klaten - Farida Yulfi Muslimah; Ahmad Noer; Lilis Siti Badriah (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2007)
This research has the aims to find out the impact of water exploitation by PT. Tirta Investama to agricultural sector, especially to farmer’s income, and introduce the importance that impact to follow up later, in Trucuk, Klaten regency. The methods of analysis used in this research are wilcoxon-different test to test differentiation farmer’s income between before and after the exploitation activities, and some indicators about environmental impact analysis that regulated by Government Regulation No.27, 1999. The result of this research shows that there is a significant differentiation between before and after exploitation of farmer’s income. Also, farmer’s income after exploitation is lower than before and the impact of the activities is very important to get wise policy.Keywords: Land water exploitation, environmental impact, farmer’s income